Kinetics of 4He gas sorption by fullerite C60. Quantum effects - Dolbin, A.V.; Esel`son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Vinnikov, N.A.; Popov, S.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The kinetics of helium gas sorption by a C60 powder and subsequent desorption of the 4He impurity from the saturated powder has been investigated in the temperature interval 2–292 K. Evidence is obtained that supports the existence of two stages in the temperature dependences of sorption and desorption. The stages account for the different times taken by helium to occupy the octahedral and tetrahedral interstices in the C60 lattice. The characteristic times of sorption and desorption coincide. It is found that the temperature dependences of the characteristictimes of occupying the octahedral and tetrahedral interstices are nonmonotonic. As the temperature islowered from 292 to 79.3 K, the characteristic times increase, which indicates a predominance of thermally activated diffusion of helium in C60. On a further decrease to T = 10 K the characteristic times reduce over an order of magnitude. Below 8 K the characteristic times of sorption and desorption are temperature-independent. Thissuggests a tunnel character of 4He diffusion in C60.